11 Oral P2Y12 inhibitors and stemi outcomes: a single centre propensity scored analysis. (June 2018) - Khan, Nazish; Martins, Joe; Wrigley, Ben; Khogali, Saib; Munir, Shahzad; Smallwood, Andrew; Nightingale, Peter; Cotton, James
Abstract : Introduction: Mechanical coronary reperfusion with primary percutaneous coronary intervention (PPCI) and concomitant oral dual antiplatelet therapy, is the preferred strategy in patients presenting with ST elevation myocardial infarction (STEMI). Currently, guidelines regarding the choice of oral P2Y12 inhibitor are conflicting. We sought to determine the impact of clopidogrel, prasugrel and ticagrelor in a real-world STEMI population on the incidence of in-hospital, 30 day and 1 year mortality, in addition to their effects on the incidence of in-hospital major bleeding episodes. Methods: A retrospective observational analysis of 2200 STEMI patients managed by PPCI between November 2011 and November 2015 was undertaken. During this period our clinical protocol changed sequentially from prescribing clopidogrel to prasugrel to ticagrelor for patients undergoing PPCI. All data were collected and verified by review of the patient clinical records. Mortality data were obtained via the Office of National Statistics. Bleeding information was taken from the clinical records and review of haematology database. Statistical analysis was two fold: standard multi-logistic regression and a second propensity score (PS) based analysis. Results: The study population n=2200 (24% female) were treated with either clopidogrel (n=570), prasugrel (n=1058) or ticagrelor (n=592). Refer to table 1 for baseline characteristics. Figures 1 and 2 demonstrate that ticagrelor treated patients had improved in-hospital (PS, p=0.001), 30 day (PS, p<0.001) and 1 year (PS, p<0.001) survival compared with prasugrel. Ticagrelor was not superior to clopidogrel for in-hospital and 30 day survival, however, was associated with reduced mortality at 1 year (PS, p=0.004). No survival differences were seen at the three time points between clopidogrel and prasugrel. These results were broadly similar whether logistic regression or propensity score analysis was used. There are no reported differences in terms of in-hospital major bleeding episodes when comparing the three oral agents (figure 2). Conclusion: This is the first clinical analysis of the three major oral P2Y12 inhibitors in STEMI patients treated with PPCI. There appear to be advantages associated with the use of ticagrelor when compared to prasugrel, in terms of mortality at all time points, and when compared to clopidogrel at 1 year.